Associations of serum folate and vitamin C levels with metabolic dysfunction-associated fatty liver disease in US adults: A nationwide cross-sectional study - Jiang, Yuqi; Cao, Huanyi; Chen, Xingying; Yu, Genfeng; Song, Cheng; Duan, Hualin; Tian, Feng; Wan, Heng; Shen, Jie (Frontiers in Public Health, 2022)
Background: Clinical research results on the relationship between folate and non-alcoholic fatty liver disease are contradictory. Metabolic dysfunction-associated fatty liver disease (MAFLD) is a recently proposed new concept. Evidence about the relationship between serum folate and MAFLD, especially considering the status of serum vitamin C, is scarce. This study aimed to investigate the association of serum folate levels with the prevalence of MAFLD, and further to analyze the potential impact of serum vitamin C status on the association between serum folate level and MAFLD. Methods: National Health and Nutrition Examination Survey (NHANES) database 2017–2018 was utilized, of which 2797 participants were included in the study. Vibration-controlled transient elastography was used to detect liver steatosis and fibrosis. Logistic regression analysis in the complex sample module was performed to illustrate the association of serum folate levels with the prevalence of MAFLD; stratification analysis by serum vitamin C status was performed as well. Results: Among all the participants, compared with participants of T1 group serum folate levels, participants in the T3 group had a lower risk of MAFLD by 47.9% [OR=0.521 (95% CI: 0.401-0.677)]. However, when participants were stratified by serum vitamin C levels, there was no association between the serum folate levels and MAFLD of participants in the T1 and T2 group. Among participants in the T3 group of vitamin C status, participants in the T3 group of serum folate had a lower risk of MAFLD by 63.6% compared with those in the T1 group [OR=0.364, (95% CI 0.147-0.903)]. Conclusions: High serum folate levels were associated with lower prevalence of MAFLD, especially in participants with sufficient vitamin C.